Pengaruh Komposisi Bahan Bakar Oli Bekas dan Minyak Goreng Bekas Terhadap Suhu Pembakaran Pada Kompor Bertekanan - Harita Nurwahyu Chamidy (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The management of waste has become a increasingly intricate matter due to the rising volume of household waste. The present study evaluates the effect of the composition of a mixture of used oil and used cooking oil as an alternative fuel on the combustion temperature in a steam pressurized stove. Four distinct variations of fuel composition were meticulously executed: 300:0, 150:150, 50:250, and 0:300. These variations were then subjected to rigorous testing, entailing the measurement of temperature at the steam output chimney section at five-minute intervals for a duration of 40 minutes. The findings indicated that augmenting the quantity of cooking oil in the mixture led to a reduction in combustion temperature. The highest recorded temperature was attained at a composition of 300:0 (pure used oil), reaching 680°C, while the lowest temperature was observed at a composition of 0:300, with a temperature of 275°C. A subsequent analysis of variance (ANOVA) revealed a statistically significant disparity in the average combustion temperatures of the distinct fuel compositions (p-value < 0.05). The composition of the pure used oil, characterized by its high hydrocarbon content and calorific value, yielded a combustion process that was more efficient and stable. In contrast, cooking oil exhibited a lower combustion efficiency. The present study lends support to the utilization of liquid waste as an alternative fuel, a practice that has the dual benefits of reducing waste volume and producing useful by-products, including heat energy and gas.